(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. La figura del “reato culturalmente motivato” e l’idea di multiculturalismo - 2. L’eterogeneità della categoria dei reati culturalmente motivati. Il principio di offensività come canone ermeneutico e veicolo di un approccio interdisciplinare - 3. Il “porto” del kirpan: l’approccio ‘fonografico’ del giudice di legittimità nell’ordinamento italiano - 4. La reasonable accomodation nell’interpretazione pluralista della Corte Suprema Canadese attraverso il caso Multani. Spunti per una comparazione - 5. L’„accomodation” alla prova del paradigma sicuritario. La vicenda del riconoscimento della personalità giuridica della comunità sikh in Italia. Rethinking the antinomy of the cultural offence. Hypotheses from a legal-philosophical perspective ABSTRACT: The essay is intends to problematize the epistemological perspective which, in the Italian system, upholds the judicial interpretation related to the cases that can be ascribed to the category of the so-called cultural offence. In this regard, the article is focused on the case-law concerning the religious practices of the sikh believer and on the legal recognition affair of Sikhism in Italy, identifying this empirical field as a privileged observatory. The topic of the analysis, through the Canadian approach, makes it possible to assess the canons of the prevailing hermeneutics in matter and to envisage hypotheses toward a rethinking of the theoretical assumptions underlying the criminal law enforcement, especially considering non offensive conduct of a religious nature.